Processus de counseling et apprentissage expérientiel - Fortin, Gilles; Chevrier, Jacques (Canadian Journal of Counselling and Psychotherapy, 2007)
The aim of this article is to highlight that the counselling process entails learning. The authors point out the similarities between the cognitive behaviours underlying the various counseling stages and those underlying Kolb's experiential learning model. They also argue that counselling models concur in their description of the essential elements of the counselling process, even though they may differ in their way of mapping it. The conclusion focuses on the practical implications of this connection by underscoring the educational dimension of counselling.